Effect of SIRT2 Inhibition on Developing Fibrosis in D-Galactose-Induced Aging Model - BAHAR, ASLI NUR (My University, 2023)
AIM: Aging is a risk factor for fibrosis and liver injury. SIRT2 inhibition has been shown to have a protective effect on the mechanism of renal interstitial fibrosis. In our study, it was aimed to determine the effect of SIRT2 inhibition by AGK-2 on liver functions and its role in the fibrosis process in the aging model caused by D-galactose (D-GAL).METHODS: A total of 32 3-month-old Sprague Dawley rats were used in the study. Rats were divided into 4 groups as Control, D-GAL, Solvent+D-GAL, D-GAL+AGK2+Solvent. D-galactose (150 mg/ kg/day), AGK-2 (10μM/bw) as a specific SIRT2 inhibitor, 4%DMSO+PBS as a solvent were applied to the experimental groups and physiological saline was applied to the control group for 10 weeks. Biochemical parameters (ALT, AST, platelet count, LDH, HDL, VLDL, total cholesterol, triglyceride) were measured in plasma.AST-ALT Ratio, AST-Platelet Ratio Index (APRI), liver index (liver weight/body weight) were calculated. SIRT2 levels in liver tissues were determined by western blot (WB) and immunohistochemical (IHC) analysis.The expression level of TGF β, β catenin, PDGFBB genes was determined by real-time-polymerase chain reaction. Histopathological scoring was performed to detect tissue damage.For statistical analysis, the data obtained from the study were presented as \"mean±standard deviation\".One-way ANOVA (post-hoc LSD) test was used to determine the intergroup differences, and Pearson correlation test was used to determine the relationshipsbetween the variables(p<0.05). RESULTS: D-Galactose administration increased AST, AST-ALT ratio, APRI, SIRT2 protein expression, TGF β, β catenin mRNA levels in liver tissue. AGK-2 application decreased all theseparameters. SIRT2 expression (WB) is positively correlated with AST,APRI index, TGF β1, β-catenin mRNA expression. SIRT2(IHC) is positively correlated with AST/ALT and APRI index.CONCLUSION: It is thought that SIRT2 inhibition may be effective in improving aging-related fibrotic changes in the liver and preventing aging-related loss of function.Keywords:D-Galactose, Fibrosis, SIRT2 inhibition, TGFβ, β catenin,Liver.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE